The New Chautauqua Game: Designing the Renewable City and Region Using E[m]ergy Accounting - Braham, William W.; Butcher, Luke; Kurtz, Jill Sornson; Roudsari, Mostapha Sadeghipour; Vyas, Janki (Journal of Environmental Accounting and Management, 2026)
This paper presents the results of a simplified method for reconfiguring a small city and rural county to support its current population on the environmental energies available within the boundaries of the county. It is configured as a game, based on the simplifying assumption that the collection and concentration of renewable energies is almost entirely a matter of surface or land area, so that a renewable economy becomes a matter of competing land uses, of tradeoffs between land used for the production of food, fuel, electricity, and so on. Emergy accounting was used to translate different forms of consumption into equivalent land areas, while the many forms of production and consumption were reduced to 29 parameters that can be varied to test alternate scenarios for the county. The results have been coded into a web site for playing the game.